Design and validation of PIP gene primer for quantitative PCR in Capsicum annuum using in silico and experimental approaches - Nurhafitri, Amanda; Suwirmen (Bioeksperimen: Jurnal Penelitian Biologi, 2026)
Capsicum annuum L. is an economically important horticultural crop whose productivity is strongly affected by drought stress. Plasma Membrane Intrinsic Protein (PIP), a member of the aquaporin gene family involved in water transport and osmotic regulation, represents a key target for drought stress studies, requiring highly specific and efficient primers for accurate gene expression analysis using quantitative PCR (qPCR). This study aimed to design and validate PIP gene primers for qPCR in C. annuum using integrated in silico and experimental approaches. Primer design was performed using NCBI Primer-BLAST based on the CaPIP reference sequence (XM_016711608.2), followed by in silico evaluation of primer specificity and secondary structure using Primer-BLAST and OligoAnalyzer. Nine primer pairs were initially generated and evaluated based on primer length, %GC, Tm, self3’ complementarity and amplicon size. Secondary structure analysis revealed strong self-dimer formation in pair 8, whereas pair 2 showed weak secondary structure within acceptable ΔG threshold (-9 kcal/mol). Experimental validation was conducted throught gradient PCR to optimize annealing temperature, followed by agarose gel 2%. Primer 2_CaPIP produced specific and clear amplification, with an optimal annealing temperature of 57.3oC. This study provides a validated CaPIP primer set suitable for qPCR-based gene expression analysis in C. annuum, supporting future molecular studies on drought stress tolerance.